FACTORY PRODUCTION UNDER BUDGETARY CONTROL. - Drucker, A. P. R. (The Accounting Review, 1930)
Abstract This article focuses on the budget program instituted by the production department. The chief problem will be to produce the goods in time for their sale. In order that this may be done, or that production and sales demand may be coordinated, an inventory record of the finished goods must be kept. These records will include a control over the minimum and maximum amounts of inventory which should be on hand. The production department may consider it best to follow the lead of the sales department by manufacturing the product for the seasonal demand and shutting down until production again becomes necessary. This is the practice in many industries. In the first place, the practice of working at a high pitch for a few months of the year is not the best way of using plant and machinery. Second, it is often more economical to buy raw materials when the season is over and the demand less. Third, it is well known that men do better work when operations are regular than when they are forced to turn out rush orders.